2023
DOI: 10.3390/ijms24054997
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota-Derived Natural Products Targeting Cancer Stem Cells: Inside the Gut Pharma Factory

Abstract: Cancer stem cells (CSCs) have drawn much attention as important tumour-initiating cells that may also be crucial for recurrence after chemotherapy. Although the activity of CSCs in various forms of cancer is complex and yet to be fully elucidated, opportunities for therapies targeting CSCs exist. CSCs are molecularly distinct from bulk tumour cells, so they can be targeted by exploiting their signature molecular pathways. Inhibiting stemness has the potential to reduce the risk posed by CSCs by limiting or eli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 283 publications
0
2
0
Order By: Relevance
“…It has been recognized that inhibition of cancer stemness can reduce the drug resistance potential of cancer cells [19]; in fact, the evolution of cancer stemness and the development of drug resistance potential interact each other [20]. Intriguingly, we found L-Theanine can signi cantly decrease the expression of cancer stemness-related markers in DDP-resistant lung cancer cells (A549/DDP, NCI-H446/DDP) but not in lung cancer cells without DDP-resistance (A549 and NCI-H446).…”
Section: Discussionmentioning
confidence: 99%
“…It has been recognized that inhibition of cancer stemness can reduce the drug resistance potential of cancer cells [19]; in fact, the evolution of cancer stemness and the development of drug resistance potential interact each other [20]. Intriguingly, we found L-Theanine can signi cantly decrease the expression of cancer stemness-related markers in DDP-resistant lung cancer cells (A549/DDP, NCI-H446/DDP) but not in lung cancer cells without DDP-resistance (A549 and NCI-H446).…”
Section: Discussionmentioning
confidence: 99%
“…revealed a specific role for IAA in the response of pancreatic cancers to chemotherapy; IAA oxidation by myeloperoxidase produced 3-methylene-2-oxindole, leading to increased reactive oxygen species levels and diminished autophagy, which ultimately reduced the proliferation of pancreatic tumor cells. 7 Additional Trp metabolites have been proposed to support chemotherapies of other cancers, 40 e.g., a role for IPA in breast cancer, also via induction of oxidative stress in tumor cells. 41 IPA, IAA, and KYN have been linked to psychological functions such as mood, appetite, and anxiety via effects on neuroinflammation, Trp uptake via the blood-brain-barrier, and Trp-to-serotonin metabolism.…”
Section: Microbial Metabolism and Role Of Metabolitesmentioning
confidence: 99%
“…Microorganisms play an indirect role in affecting the emergence, natural course, and/or severity of various cancers. For instance, microbes in the gut influence dormant cancer cells that may cause disease recurrence [2]. Predominantly, research connecting microbes and cancer has focused on bacteria and their involvement in different cancers, with a few studies also exploring potential links with fungi and viruses [2].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, microbes in the gut influence dormant cancer cells that may cause disease recurrence [2]. Predominantly, research connecting microbes and cancer has focused on bacteria and their involvement in different cancers, with a few studies also exploring potential links with fungi and viruses [2]. For example, research has indicated that metabolites from certain archaea, mainly from the Euryarchaeota phylum and the TACK superphylum, are linked to numerous cancers, despite these microbes being typically overlooked due to their rarity.…”
Section: Introductionmentioning
confidence: 99%